Addressing the unmet need for a comprehensive lung cancer registry in Romania - Olteanu, Gheorghe-Emilian; Oancea, Cristian Iulian; Catalin, Marian; Trifa, Adrian Pavel; Dascalu, Stefan (Frontiers in Oncology, 2023)
In this perspective article, we describe the vital need for a well-organized cancer registry in Romania, where lung cancer prevalence and mortality rates are alarmingly high. We discuss contributing factors such as increased use of chest X-rays and CT scans during the COVID-19 pandemic and delayed diagnoses due to limited medical care access. With the nation's characteristically limited access to healthcare, it is plausible that the surge in acute imaging for COVID-19 has inadvertently resulted in a higher detection rate of lung cancer. This inadvertent early detection underscores the vital need for a well-organized cancer registry in Romania, where lung cancer prevalence and mortality rates are alarmingly high. Although impactful, these factors are not the primary causes of the high lung cancer cases in the country. We provide an overview of current options and propose future perspectives for epidemiological monitoring of lung cancer patients in Romania, aiming to enhance patient care, bolster research, and promote data-driven policy-making. While our primary focus is establishing a national registry for lung cancer, we address challenges, considerations, and best practices applicable to all cancer types. Through our proposed strategies and recommendations, we aim to contribute to the development and improvement of a comprehensive national cancer registry system in Romania.